IN-DEPTH ANALYSIS OF SOCIO-ECONOMIC AND CULTURAL REFORMS IN UZBEKISTAN DURING THE YEARS OF INDEPENDENCE - Mengboyeva Shodiya,; Jumanazarova Izzatbibi, (Ustozlar uchun, 2025)
Since achieving independence in 1991, the Republic of Uzbekistan has embarked on a profound journey of transformation. This paper provides an in-depth analysis of the critical reforms undertaken in various sectors including politics, economy, education, healthcare, culture, and international relations. By evaluating these efforts within both domestic and global contexts, the paper highlights how Uzbekistan is shaping a sustainable and modern state. The study further explores the country’s strategic shift toward democratic governance, market liberalization, and social development. The analysis relies on national policy documents, international reports, and scholarly perspectives.